The ‘Pylus complex’ sensu Opitz revisited (Coleoptera: Cleridae: Korynetinae): non-homogeneity of its genera addressed by alternative species-assignment hypothesis - Bartlett, Justin S. (Zootaxa, 2024)
Apparent superficial non-homogeneity of species assigned to the genera Apopylus Kolibáč, Fallopylus Opitz and Pylus Newman prompted reassessment of genus characters and species assignment of those genera plus Parapylus Blackburn and Pseudopylus Opitz, all of which were defined by Opitz (2015) primarily on the number of tibial spurs. Morphological investigation resulted in discovery of suites of correlating character state pairs providing more robust evidence for monophyly of the genera under study than tibial spurs alone. On this basis, genus definitions were revised, and species assigned accordingly to the newly defined genera. Taxonomic changes proposed include synonymy of Fallopylus Opitz, 2012 new synonym and Pseudopylus Opitz, 2012 new synonym with Pylus Newman, 1841, plus the following new combinations: Apopylus astrictus (Opitz, 2015) new combination (transferred from Fallopylus); Apopylus creperus (Opitz, 2015) new combination (transferred from Fallopylus); Apopylus leptofustus (Opitz, 2015) new combination (transferred from Fallopylus); Apopylus redactus (Opitz, 2015) new combination (transferred from Fallopylus); Pylus apterus (Opitz, 2015) new combination (transferred from Pseudopylus); Pylus cavus (Opitz, 2015) new combination (transferred from Fallopylus); Pylus cruslumus (Opitz, 2015) new combination (transferred from Apopylus); Pylus kolibaci (Opitz, 2015) new combination (transferred from Apopylus); Pylus nactus (Opitz, 2015) new combination (transferred from Apopylus). Pylus okei Elston, 1929 and Pylus pallipes Macleay, 1872 are returned to their original combinations from Apopylus and Fallopylus respectively. In addition to evidence for the monophyly of genera being based on more robust lines of morphological evidence, the newly defined genera are also more obviously homogenous, with superficially similar looking insects now grouped together.